Central bank independence and conservatism under uncertainty: Substitutes or complements? - Carsten Hefeker; Blandine Zimmer (Verein für Socialpolitik, 2010)
This paper revisits the trade-off between central bank independence and conservatism using a New Keynesian model with uncertainty about the central banker's output gap target. It is shown that when this uncertainty is high, the trade-off no longer holds. In this case, the optimal combination between independence and conservatism is characterised by complementarity.
Keywords: E52; E58; F33; 330; Central bank independence; Conservatism; Transparency of monetary policy